Theology, Medicalization, and Risk: Observations from the New Testament - Rowe, Christopher Kavin (Christian bioethics, 2023)
This article reflects on the intersection of the New Testament’s witness with current questions of illness, medication, risk, luck, death, and hope. Drawing principally on the Gospel of Matthew and the letters of Paul, I argue that, for Christians, hope in the resurrection—not the ability to avoid suffering and death—provides the best context for prudential judgment in light of the inscrutability of the future and the concomitant opacity that attends medical decision-making. We do not and will not know what we would need to know in order to make decisions we can count on with surety, and we thus read Scripture in order to become the people who can make wise judgments in the meantime called hope.